Performance analysis of building integrated photovoltaic (BIPV) for commercial buildings in Urban Area - Barman, Anirudha; Mannan, Muiz; Ahmed, Sharif; Mishu, Oumma Marium (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.